2023
DOI: 10.47102/annals-acadmedsg.2022458
|View full text |Cite
|
Sign up to set email alerts
|

Early COVID-19 booster is beneficial in cancer patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and its corresponding coronavirus disease was first reported as a cluster of pneumonia cases in Wuhan, China, on 31 December 2019 1 and led to an unprecedented pandemic in modern times. It quickly overwhelmed healthcare s y s t e m s a r o u n d t h e w o r l d , a n d r e n d e r e d immunocompromised patients, such as those with cancer, particularly vulnerable to severe infections.Also unprecedented was the rapid development of several h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…A systemic review has demonstrated that booster doses of COVID-19 vaccines are effective in improving seroconversion and antibody levels; however, patients with haematological cancer consistently demonstrated a poorer response to booster vaccines than patients with solid cancers [ 9 ]. Similar results after an early COVID-19 booster dose were reported by Samol J. et al [ 10 ]. However, there is a paucity of data on the serological response to and safety of a fourth dose of an mRNA COVID-19 vaccine in patients with cancer in active treatment [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…A systemic review has demonstrated that booster doses of COVID-19 vaccines are effective in improving seroconversion and antibody levels; however, patients with haematological cancer consistently demonstrated a poorer response to booster vaccines than patients with solid cancers [ 9 ]. Similar results after an early COVID-19 booster dose were reported by Samol J. et al [ 10 ]. However, there is a paucity of data on the serological response to and safety of a fourth dose of an mRNA COVID-19 vaccine in patients with cancer in active treatment [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 89%
“…It is well known that the prevention of the higher risk of severe COVID-19 and poor outcomes is crucial for patients with cancer, with vaccination being the most effective method for achieving this goal [ 9 , 11 ]. The clinical efficacy of COVID-19 vaccination in reducing the rates of symptomatic infections and severe outcomes has been described [ 9 , 10 , 11 , 12 ] and the results of third and fourth boosters have been reported to enhance protection in almost all immunocompromised patients [ 9 ]. However, there is a paucity of evidence that a fourth booster dose of COVID-19 vaccines is effective in improving antibody levels and is safe in patients with solid tumors and in active treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation